Evaluation of subacute toxicity of aqueous extarct from capitula of Solidago chilensis in mice - Bucciarelli, Alejandro (2010)
Solidago species have been used in folk medicine for the treatment of several diseases. In South America, the most abundant species is Solidago chilensis Meyen (Asteraceae), widely used in traditional medicine of several countries, where is usually employed as a diuretic, analgesic, anti-inflammatory, and to treat gastrointestinal disorders (1). We have recently reported that aqueous extracts from inflorescences of S. chilensis protected gastric mucosa in mice subjected to an ethanol-induced gastric ulcer model (2). However, there are no toxicological studies available which would be necessary in order to confirm the safe usage of the plant. For this reason, the aim of the present work was to study the subacute oral toxicity of the aqueous extract from inflorescences of S. chilensis after a 28-day repeated exposure in mice by means of a Functional Observational Battery (FOB) and by assessing the motor activity in an open field. Materials and Methods The experiment was conduced according to the protocols described by OECD (3). A group of healthy CF1 mice (8 males and 8 females) were daily exposed to 1000 mg/kg of body weight of the extract mixed with the standard food for 28 days. A control group was fed only with the standard diet. All the animals were weekly observed for signs of toxicity. At the end of the exposure, behavioral and functional parameters were evaluated through a FOB, which included a thorough description of the animals’ appearance, behavior and functional integrity. This was assessed through observations in the home cage, while animals were moving freely in an open field, and through manipulative tests. The motor activity was assessed in an open field whose floor was divided into squares. The number of squares entered by mice with all four paws, rearings, groomings and fecal boluses were scored for 15 min. Results The subacute exposure to S. chilensis did not produce alterations in all parameters evaluated in the FOB or during the manipulative tests. No significant differences were observed between control and experimental groups in the different parameters analyzed during home cage, hand-held and open field observations (P>0.05). Motor activity evaluations in the square open field indicated that the subacute exposure did not modify neither the number of squares crossed nor rearings after the exposure. No significant differences were observed between control and experimental groups in emotionality parameters as the number of groomings and fecal boluses (P>0.05). Conclusions This study demonstrates that the aqueous extract from Solidago chilensis does not produce neurotoxicity due to it does not affect the functionality of the nervous system at neuromuscular, sensory and autonomic level. Considering the results it was demonstrated that the oral administration of the aqueous extract of the plant does not produce toxicity by subacute exposure in mice. This effect has already been observed in previous studies after the acute exposure in mice (4). Despite the lack of toxicity indicates that the possible therapeutic use of the plant may be safe, future research like potential chronic toxicity associated with this extract will need to be evaluated through long-term bioassays in order to ensure its safety.